EFFECT OF WORK LIFE BALANCE (WLB) AND WORKLOAD ON EMPLOYEE PERFORMANCE WITH MOTIVATION AS A MODERATION VARIABLE (Study on Employees of PT. Bukit Asam (Persero), Tbk Tarahan Harbor Unit) - Ayang Nurma Diana; Habibullah Jimad2; Mirwan Karim (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2022)
PT Bukit Asam (Persero) Tbk. Tarahan Port Unit (PTBA) is the best mining industry and coal supplier in Indonesia. PTBA considers employees as assets, because employee performance is an important thing that supports the achievement of company targets. PTBA for the last five years has been faced with the complexity of the problem of declining profits which is thought to be caused by the quality of its human resources, so that it is a management demand to continue to improve employee performance because employee performance is an important thing that supports the achievement of company targets. This study aims to determine the effect of Work Life Balance (WLB) and workload on the performance of employees of PT Bukit Asam (Persero) Tbk. Tarahan Port Unit with Motivation as a moderating variable. The research method used is quantitative, which is a process of finding knowledge that uses data in the form of numbers as a tool to analyze information about what you want to know. In this study using a questionnaire with a Likert scale. The research population was 203 people and the sample was taken as many as 160 people. Data analysis used Moderated Regression Analysis (MRA) with IBM SPSS 26 analysis tool. The results showed that work life balance and workload had a positive effect on employee performance. Meanwhile, work motivation cannot moderate the effect of work life balance on employee performance but can moderate the effect of workload on employee performance. The leadership of PT Bukit Asam (Persero) Tbk. Tarahan Port Unit is expected to increase motivation and optimize workload for employees so that their performance can increase.